Some internal and external effects of the rise in the price of oil - L. IZZO; L. SPAVENTA (PSL Quarterly Review, 2013)
The work looks at the rise in the price of crude oil, elucidating some economic implications of the issues which a large number of economies will have to face in the near future. The authors first consider the primary impact of the rise in the price of crude on the economy of an importing country considered in isolation. A simple model shows a very sizeable deflationary effect which, to a large extent, can only be offset as a result of deliberate policy decisions. It is also shown how each importing country’s decisions in this matter affect the situation of all others. Some aspects of the international payments problem are then dealt with.